From Coarse Grained to Atomistic: A Serial Multiscale Approach to Membrane Protein Simulations - Stansfeld, P; Sansom, M (2011)
Coarse-grained molecular dynamics provides a means for simulating the assembly and the interactions of membrane protein/lipid complexes at a reduced level of representation, allowing longer and larger simulations. We describe a fragment-based protocol for converting membrane simulation systems, comprising a membrane protein embedded in a phospholipid bilayer, from coarse-grained to atomistic resolution, for further refinement and analysis via atomistic simulations. Overall, this provides a method for generating an accurate and well equilibrated membrane protein/lipid complex. We exemplify the protocol using the acid-sensing/amiloride-sensitive ion channel protein (ASIC) channel protein, a trimeric integral membrane protein. The method is further evaluated using a test set of 10 different membrane proteins of differing size and complexity. Simulations are assessed in terms of protein conformational drift, lipid/protein interactions, and lipid dynamics. © 2011 American Chemical Society.